1986
DOI: 10.1177/000841748605300505
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Occupational Therapy Students: A Validity Study

Abstract: Objective evaluation of clinical competence is always a difficult task. Many attempts have been made to design an instrument for such evaluation. and Performance Evaluation of Occupational Therapy Students (PEOTS) is such an instrument. It was designed as a criterion-referenced evaluation of performance in four broad areas of clinical competence: professional interaction, assessment, programming and treatment. This instrument has enjoyed fairly broad acceptance based on its face validity alone. The purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Results from the validity study (Ernest & Polatajko, 1986) also indicated that the majority of items in the PEOTS were used frequently, suggesting good content validity of the evaluation instrument. A second study by Ernest (1988) demonstrated that many of the 122 PEOTS skills were generic or general in nature.…”
Section: Validity Of the Peotsmentioning
confidence: 88%
See 4 more Smart Citations
“…Results from the validity study (Ernest & Polatajko, 1986) also indicated that the majority of items in the PEOTS were used frequently, suggesting good content validity of the evaluation instrument. A second study by Ernest (1988) demonstrated that many of the 122 PEOTS skills were generic or general in nature.…”
Section: Validity Of the Peotsmentioning
confidence: 88%
“…) involved and "deals with assessing the degree of accuracy in measuring the underlying elements (constructs) of a scale" (Adams & Schvaneveldt, 1985, p.84). Good construct validity of the PEOTS was suggested in the study by Ernest & Polatajko (1986) since the criteria set for new graduates was achieved. On many of the items, in fact, new graduates demonstrated a higher level of functioning than expected and scores appeared to cluster at the higher end of the rating scale.…”
Section: Validity Of the Peotsmentioning
confidence: 99%
See 3 more Smart Citations